MODERN CHRISTIAN THEOLOGY : AN ANALYSIS AT DR KOSUKE KOYAMA'S PERSPECTIVE - RAMSIDA N SIBURIAN; ROBINHOT SIHOMBING (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Koyama's thoughts are really interesting for us to help understand the diversity in a culture. This paper will discuss how his thoughts are associated with the reality of modernity which is increasingly running fast. The results of the study of Koyama's thoughts when related to the realities of life, found that modern Christian theological thinking in Asia (in this case is the Thai context where Koyama lives) is related to the economic, social, and political situation in Asia which is still experiencing poverty, underdevelopment, and poverty. oppression from the rulers. In addition, Christians in Asia live side by side with adherents of other religions with natural interactions.